Optimization of fuzzy controllers for a radial distribution network - Espitia Cuchango, Helbert Eduardo; Machón González, Iván; López García, Hilario; Díaz González, Domingo Guzmán (Visión electrónica, 2019)
Energy distribution systems present alterations in the voltage profile in their nodes when distributed generation elements are installed. As a consequence, tension can be risen in a level beyond the admissible. This paper presents the optimization to three fuzzy controllers located in a distribution network with radial topology. The optimization of each controller is performed using the maximum descent algorithm, which is separately carried out; thus, having a distributed approach. The interaction between generators is considered to perform this process; the results show that the adjustment of the controllers is achieved